On optimal layering and bandwidth allocation for multisession video broadcasting. - Jiangchuan Liu (IEEE Transactions on wireless communications)
For video broadcasting applications in a wireless environment, layered transmission is an effective approach to support heterogeneous receivers with varying bandwidth requirements. There are several important issues that need to be addressed for such layered video broadcasting systems. At the session level, it is not clear how to allocate bandwidth resources among competing video sessions. For a session with a given bandwidth, questions such as how to set up the video layering structure (i.e., number of layers) and how much bandwidth should be allocated to each layer remain to be answered. The solutions to these questions are further complicated by practical issues such as uneven popularity among video sessions and video layering overhead. This paper presents a systematic study to address these issues for a layered video broadcasting system in a wireless environment. The approach is to employ a generic utility function for each receiver under each video session. They cast the joint problem of layering and bandwidth allocation (among sessions and layers) into an optimization problem of total system utility among all the receivers. By using a simple two-step decomposition of intersession and intrasession optimization, they derive efficient algorithms to solve the optimal layering and bandwidth allocation problem. Practical issues for deploying the optimal algorithm in typical wireless networks are also discussed. Simulation results show that the optimal layering and bandwidth allocation improves the total system utility under various settings.